2013
DOI: 10.5194/cp-9-983-2013
|View full text |Cite
|
Sign up to set email alerts
|

Glacial–interglacial dynamics of Antarctic firn columns: comparison between simulations and ice core air-δ<sup>15</sup>N measurements

Abstract: Abstract. Correct estimation of the firn lock-in depth is essential for correctly linking gas and ice chronologies in ice core studies. Here, two approaches to constrain the firn depth evolution in Antarctica are presented over the last deglaciation: outputs of a firn densification model, and measurements of δ15N of N2 in air trapped in ice core, assuming that δ15N is only affected by gravitational fractionation in the firn column. Since the firn densification process is largely governed by surface temperature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 60 publications
4
35
0
Order By: Relevance
“…This comparison serves as a prerequisite for the comparison with outputs of the revised model over the same period for the same polar sites. The comparison between the old LGGE model and δ 15 N data over the last deglaciation shows the same patterns already discussed in Capron et al (2013). At Greenland sites, there is an excellent agreement between model and data showing both the decrease in the mean δ 15 N level between the LGM and the Holocene and the ∼ 0.1 ‰ peaks in δ 15 N associated with the abrupt temperature changes (end of the Younger Dryas, Bølling-Allerød, Dansgaard-Oeschger 2, 3, and 4; Figs.…”
Section: Transient Run With the Old Modelsupporting
confidence: 57%
See 2 more Smart Citations
“…This comparison serves as a prerequisite for the comparison with outputs of the revised model over the same period for the same polar sites. The comparison between the old LGGE model and δ 15 N data over the last deglaciation shows the same patterns already discussed in Capron et al (2013). At Greenland sites, there is an excellent agreement between model and data showing both the decrease in the mean δ 15 N level between the LGM and the Holocene and the ∼ 0.1 ‰ peaks in δ 15 N associated with the abrupt temperature changes (end of the Younger Dryas, Bølling-Allerød, Dansgaard-Oeschger 2, 3, and 4; Figs.…”
Section: Transient Run With the Old Modelsupporting
confidence: 57%
“…We have used this estimate of asymmetric uncertainty on the amplitude of temperature change during deglaciation in our study. Recent studies have also suggested that the relationships between water isotopes and temperature and between water isotopes and accumulation rate can be applied with confidence in Antarctica for glacial temperature reconstruction (Cauquoin et al, 2015), while one should be cautious for interglacial temperature reconstruction with warmer conditions than today (Sime et al, 2009). Finally, a recent estimate of the deglacial temperature increase based on δ 15 N measurements at WAIS led to a 11.3 • C temperature increase over the last deglaciation (1 • C warming to be attributed to change in elevation).…”
Section: Input Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated by δ 15 N measurements as a proxy for firn height (Sowers et al, 1992), up-to-date firn air models seem to have difficulties to estimate past lock-in depths for the East Antarctic plateau (Landais et al, 2006;Capron et al, 2013) and to synchronize age dating of individual ice cores (Parrenin et al, 2012). We suggest that incorporation of our results will help to overcome these problems, as current approaches are based on temperature-dependent lockin (Martinerie et al, 1992) and the Barnola model (Goujon et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These modeled chronologies are based on the current knowledge of bubble trapping in polar firn and are particularly sensitive to the critical porosity via the assumed temperature dependence. Deviations from the simple relationships used to reconstruct past temperatures and accumulation rates from the water isotopic composition have been suggested as a possible explanation (Landais et al, 2006), while the hypothesis of a large glacial convective zone as an important factor has been ruled out (Capron et al, 2013). Recently, the inclusion of impurity effects has reduced the mismatch for East Antarctic sites; however, it reduces the agreement between modeled and measured δ 15 N for high-accumulation sites (Breant et al, 2017).…”
Section: Introductionmentioning
confidence: 99%